Relevance of Additional Immunohistochemical Markers in the Differential Diagnosis of Small B-Cell Lymphomas: A Case-Control Study - Kivrak, Hale; Yuksel, Seher; Ates, Can; Merter, Mustafa; Kaygusuz, Gulsah; Ozcan, Muhit; Kuzu, Isinsu (Galenos Publ House, 2022)
Objective: Clinical and pathological differential diagnosis of small B-cell lymphomas (SBCLs) is still controversial and may be difficult due to their overlapping morphology, phenotype, and differentiation to plasma cells. We aimed to examine the expression of the immune receptor translocation-associated protein 1 (IRTA1), myeloid cell nuclear differentiation antigen (MNDA), lymphoid enhancer-binding factor-1 (LEF1), and stathmin 1 (STMN1) markers in SBCL cases involving different sites that may have plasma cell differentiation. Materials and Methods: We studied 154 tissue samples with lymphoma involvement from 116 patients and evaluated the staining distribution of the markers. Expressions were evaluated in 21 chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL), 7 follicular lymphoma (FL), 14 nodal marginal zone lymphoma, 17 extranodal marginal zone lymphoma, 55 splenic marginal zone lymphoma, 22 marginal zone lymphoma-not otherwise specified, and 18 lymphoplasmacytic lymphoma/Waldenstrom macroglobulinemia cases by immunohistochemistry. Results: The results confirmed that LEF1 was the most sensitive and specific marker for CLL/SLL and STMN1 was the most sensitive and specific marker for FL (p<0.001). MNDA and IRTA1 were useful markers to distinguish marginal zone lymphomas. Conclusion: Our results suggest that LEF1 for CLL/SLL and STMN1 for FL are reliable markers. LEF1, MNDA, STMN1, and IRTA1 are helpful with other routinely used immunohistochemical markers in a diagnostic algorithm considering their limitations.
Küçük B-Hücreli Lenfomalarda Ek İmmünohistokimyasal Belirteçlerin Ayırıcı Tanıdaki Yeri: Bir Olgu-Kontrol Çalışması
Keywords: Small B-cell lymphoma; MNDA; LEF1; Stathmin 1; IRTA1